The effect of anemia educational videos on the knowledge and attitudes of adolescent girls at State Junior High School 4, West Aceh - Susanti, Ita; Damayanti, Siti; Satria, Orita; Apriani, Fitri; Nasution, Nurromsyah (Journal of Health and Therapy, 2025)
Anemia continues to pose a serious global health concern and is particularly widespread in developing countries such as Indonesia. Adolescent girls face a heightened risk of iron deficiency anemia due to menstrual blood loss, which leads to nearly double the iron depletion experienced by boys. Video-based educational interventions provide an accessible means of improving young people’s knowledge and attitudes toward anemia prevention. This study examined the effect of animated educational videos on the knowledge and attitudes of adolescent girls regarding anemia. A total of 71 participants were involved, and data collection took place in June 2025 using a structured questionnaire assessing knowledge and attitudes toward anemia. Univariate and bivariate analyses were conducted, and the Wilcoxon test was applied to determine changes before and after the intervention. The results showed significant improvements in both knowledge and attitudes after participants viewed the animated video. These findings indicate that animated video education is an effective strategy for strengthening adolescents’ understanding and fostering positive attitudes toward anemia prevention. Health workers are encouraged to expand the use of video-based health promotion to support anemia prevention initiatives among young people.